Molecular characters of melon (Cucumis melo L. ‘Kinaya’) using inter simple sequence repeat - Budi Setiadi Daryono; Puti Hana Ramadhani; Esty Nidianti (Biogenesis: Jurnal Ilmiah Biologi, 2021)
Cultivar ‘Kinaya’ is a melon produced from breeding between ‘Sonya’ and ‘Kinanti’. This study on phenotypic and molecular characters is carried out to support ‘Kinaya’ as a superior cultivar. Our study aimed to analyze the genetic variation of the melon ‘Kinaya Bulat Kuning’ and ‘Kinaya Kuning Lonjong’ and its parental ‘Sonya’ and ‘Kinanti’. The research was conducted in the Greenhouse of Mutihan, D.I.Yogyakarta, and the Laboratory of Genetics and Breeding, Faculty of Biology, Universitas Gadjah Mada. Quantitative characters were determined by morphometric comparisons, fruit weights, and the number of seeds. Qualitative characters included fruit color, fruit skin color, aroma, texture, and taste. The molecular characterization method was inter simple sequence repeat (ISSR) and included DNA isolation, spectrophotometry, amplification of DNA target using PCR, and visualization of DNA target. Molecular characters were analyzed using spectrophotometry and visualization of DNA bands by electrophoresis using the MVSP 3.1 program. PCR used four random primers such as UBC 807, 809, 810, and 812, which obtained 11 polymorphic and 12 monomorphic DNA bands with a polymorphism rate of 47.8%. It is known that the cultivar ‘Kinaya’ has a similarity of 72% with its inductees ‘Sonya’ and ‘Kinanti’.